hAMSCs regulate EMT in the progression of experimental pulmonary fibrosis through delivering miR-181a-5p targeting TGFBR1 - Yanyang Wang; Chan Liu; Nuoxin Wang; Dong Weng; Yan Zhao; Hongyu Yang; Haoyuan Wang; Shangfu Xu; Jianmei Gao; Changhui Lang; Zhenhai Fan; Limei Yu; et al. (Stem Cell Research & Therapy)
Abstract Background Pulmonary fibrosis (PF) is a common and multidimensional devastating interstitial lung disease. The development of novel and more effective interventions for PF is an urgent clinical need. A previous study has found that miR-181a-5p plays an important role in the development of PF, and human amniotic mesenchymal stem cells (hAMSCs) exert potent therapeutic potential on PF. However, whether hAMSCs act on PF by delivering miR-181a-5p and its detailed mechanism still remain unknown. Thus, this study was designed to investigate the underlying possible mechanism of hAMSCs on PF in bleomycin (BLM)-induced mouse PF model, and a co-culture system of hAMSCs and A549 cells epithelial mesenchymal transition (EMT) model, focusing on its effects on collagen deposition, EMT, and epithelial cell cycle regulation. Methods hAMSCs with different miR-181a-5p expression levels were constructed. BLM (4 mg/kg) was used to create a PF model, while TGF-β1 was used to induce A549 cells to construct an EMT model. Furthermore, the effects of different miR-181a-5p expression in hAMSCs on collagen deposition and EMT during lung fibrosis were assessed in vivo and in vitro. Results We found that hAMSCs exerted anti-fibrotic effect in BLM-induced mouse PF model. Moreover, hAMSCs also exerted protective effect on TGFβ1-induced A549 cell EMT model. Furthermore, hAMSCs ameliorated PF by promoting epithelial cell proliferation, reducing epithelial cell apoptosis, and attenuating EMT of epithelial cells through paracrine effects. hAMSCs regulated EMT in PF through delivering miR-181a-5p targeting TGFBR1. Conclusions Our findings reveal for the first time that hAMSCs inhibit PF by promoting epithelial cell proliferation, reducing epithelial cell apoptosis, and attenuating EMT. Mechanistically, the therapeutic effect of hMASCs on PF is achieved through delivering miR-181a-5p targeting TGFBR1.